Venous thromboembolism with EGFR monoclonal antibody necitumumab in stage IV non-small cell lung cancer: A retrospective cohort analysis. Issue 167 (July 2018) - Young, Kelvin; Paz-Ares, Luis; Thatcher, Nick; Spigel, David R.; Shahidi, Javad; Soldatenkova, Victoria; Grau, Gerrit; Kurek, Raffael; Shepherd, Frances A.
Abstract: Introduction: Metastatic non-small cell lung cancer (NSCLC) is a recognized risk factor for VTE. Some systemic treatments may increase this risk further. Here, we present the risk of VTE and its prognostic significance for patients treated with chemotherapy (chemo) and the EGFR monoclonal antibody necitumumab (neci) for metastatic NSCLC. Methods: Four trials of 1st-line treatment for Stage IV NSCLC were analyzed: two randomized phase 3 studies of cisplatin/gemcitabine ±neci in squamous NSCLC (SQUIRE: N = 1079) and cisplatin/pemetrexed ±neci in non-squamous NSCLC (INSPIRE: N = 616); JFCL ( N = 161), a randomized phase 2 trial of carboplatin/paclitaxel ±neci in squamous NSCLC; and JFCK ( N = 61), a single arm phase 2 trial of cisplatin/gemcitabine +neci in squamous NSCLC. A Cox proportional hazards model with VTE as a time-dependent covariate was used for overall survival (OS) analyses. Results: Neci + chemo was associated with an increased risk of VTE (Relative Risk [RR]: 1.579; 95% CI: 1.155–2.158). History of VTE (RR: 1.899; 95% CI: 1.142–3.156) and prior cardiac/cardiovascular events (RR: 1.514; 95% CI: 1.102–2.082) were associated with increased risk of VTE. Decreased VTE risk was seen with: male sex (RR: 0.696; 95% CI: 0.502–0.964), eastern European geographic region (RR: 0.387; 95% CI: 0.267–0.562) and squamous cell pathology (RR: 0.653; 95% CI: 0.483–0.883). VTE occurrence showed no association with OS (HR: 1.121; 95% CI: 0.930–1.351). Conclusion: Our data suggest that certain patient characteristics such as prior history of VTE and non-squamous histology might be associated with an increased risk of on-treatment VTE in NSCLC, although in this study, overall survival was not affected. Further studies to develop measures for identifying high-risk patients are needed to inform treatment decisions as well as VTE management and prophylaxis. Highlights: Venous thrombosis risk is greater with necitumumab in non-small cell lung cancer. Mortality is not affected by the presence of venous thrombosis in these patients. The Khorana risk score does not seem to be relevant in this patient population.